Gegen, or Translating the (En)counter. Issue 2 (August 2015) - Herbrechter, Stefan
<x content-type="archive" xml:space="preserve">Abstract</x> The article discusses the notion of the 'post-literary' and 'countertextuality' by reconnecting them to previous theoretical contexts that have dealt with the question of 'text' and 'textuality'. The word 'countertextuality' evokes the rise and fall of poststructuralism and deconstruction within the globalised, Anglo-American-dominated humanities. In order to see what countertextuality might mean or do for the current context the article briefly returns to the beginnings of French theory in the humanities from the 1970s onwards and critically evaluates the challenges these are facing today. It asks what kind of 'object' [Gegenstand] a (counter)text might be, under the current conditions of digitalisation. Against the focus on the countertextual as the result of a technology-driven transformation of text into code the article concludes by foregrounding the gesture and dynamics of 'countering' as a process of translation and its intrinsic issues of untranslatability.